The development of the typical islamic schools administrations in Côte d'Ivoire In light of the overall quality standards - Abdul Hakim, Abdullah (2016)
The study aimed to identify the most important quality standards in the areas of leadership, strategic planning,human, material and financial resources, and curriculum,educational process improve the performance of the typical Islamic schools administrations in Côte d'Ivoire,the study showed that the most comprehensive quality standards to improve the performance of the typical Islamic schools administrations in Côte d'Ivoire,the most prominent in:Clear plan in the administration,Provide classroom and school departments with the basic tools necessary fittings,and provide qualified personnel for teaching and administrative work,and Suitable contents of the curriculum to the needs of society and the requirements of the labor market,and enhance the curriculum skills of creativity and innovation among students,the study recommended that schools adopt comprehensive quality standards departments and disseminated among those working.